Liṅga Purāṇa : A Socio-cultural Survey - Sinak, Sanit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 2 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2019)
The objective of the current article is to briefly survey and study of the socio-cultural aspects in the lingapurana for further critical study in another aspect of the Lingapurana such as language or geography etc. The results of survey found that in the Lingapurana there are socio-cultural aspects such as 1) philosophy 2) the geography of ancient planet 3) religion or holy places 4) major principle and 5) yoga system.